Neurocognitive Outcome After Treatment With(out) ECMO for Neonatal Critical Respiratory or Cardiac Failure - Schiller, Raisa M.; Tibboel, Dick (Frontiers in Pediatrics, 2019)
Over the years, it has become clear that children growing up after neonatal critical illness are at high risk of long-term neurocognitive deficits that impact their school performance and daily life activities. Although the pathophysiological mechanisms remain largely unknown, emerging evidence seems to suggest that long-term neuropsychological deficits following neonatal critical illness are not associated with the type of treatment, such as extracorporeal membrane oxygenation (ECMO), but rather with underlying disease processes. In this review, neurocognitive outcome and brain pathology following neonatal critical respiratory and cardiac illness, either treated with or without ECMO, are described and compared in order to gain insight into potential underlying pathophysiological mechanisms. Putting these findings together, it becomes apparent that both children with complex congenital heart disease and children who survived severe respiratory failure are at risk of neurocognitive deficits later in life. Neurorehabilitation strategies, such as Cogmed working-memory training, are discussed. While prevention of neurocognitive deficits altogether should be strived for in the future, this is not realistic at this moment. It is therefore of great importance that children growing up after neonatal critical illness receive long-term care that includes psychoeducation and personalized practical tools that can be used to improve their daily life activities.